ALPHA PSYCHIATRY 2023
DOI: 10.5152/alphapsychiatry.2023.22976
|View full text |Cite
|
Sign up to set email alerts
|

Do Children with Attention Deficit and Hyperactivity Disorder Present with Different Spatio-Temporal Gait Parameters? An Evaluation of the Relationship Between Gait and Gross Motor Skills

Abstract: Objective: The aim of the current study was to compare the spatio-temporal parameters of gait and gross motor skills in children with attention deficit hyperactivity disorder-combined type with those of typically developing children and to search the effect of motor skills on gait parameters in children with attention deficit hyperactivity disorder-combined type. Methods: A total of 50 children (n = 25 attention deficit hyperactivity disorder-combined type, n = 25 typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Spatiotemporal parameters of children with different mental disorders were previously investigated and compared to the data of their healthy peers. Other studies confirmed that children with attention deficit and hyperactivity disorder performed worse in gait parameters such as velocity, step, and stride length [33].…”
Section: Discussionmentioning
confidence: 70%
“…Spatiotemporal parameters of children with different mental disorders were previously investigated and compared to the data of their healthy peers. Other studies confirmed that children with attention deficit and hyperactivity disorder performed worse in gait parameters such as velocity, step, and stride length [33].…”
Section: Discussionmentioning
confidence: 70%
“… 6 It is also known that the majority of children with ADHD experience motor skill problems. 7 A recent study has shown that most children with ADHD still have residual symptoms in adulthood. 8 Compared with healthy adults, adult ADHD has shown obvious deficiencies in many aspects such as organization, time management, activation work, as well as maintaining attention.…”
Section: Introductionmentioning
confidence: 99%